Construir para integrar, sanear para construir: a edificação da Estrada de Ferro Madeira-Mamoré e o sanitarismo na fronteira noroeste do Brasil (1903-1913) - Nascimento, Thais Teixeira do (2022)
The construction of the Madeira-Mamoré railway (1907-1912) was an undertaking conceived by the Bolivian government in the 19th century. Between 1878 and 1879, there was the first attempt at construction – in partnership with the Brazilian imperial government – ​​in which the first seven kilometers of the railway line were built. The project, however, was not completed due to the constant illness and death of workers during the work. After this failed attempt, the enterprise was abandoned, being resumed again 28 years later as one of the indemnities from Brazil to Bolivia, for the cession of Acre, as agreed in the Treaty of Petrópolis (1903). This master's thesis, in turn, aims to problematize how the enterprise was consolidated during political conflicts and serious health problems. After all the analysis carried out throughout the dissertation, it was possible to perceive that the lack of public policies and effective works for the sanitation of the place was responsible for the potentiation of the deaths that occurred during the construction of the EFMM, being this one of the reasons for the creation of nicknames such as “Ferrovia da Morte” or “Ferrovia do Diabo” for the enterprise.